Descriptive Study: Attitude and Behaviour Regarding Oral Corticosteroid Use in Bebita Clinic Cicurug, Sukabumi in 2019 - Nabila, Audia Nizhma; Tubarad, Gladys Dwiani Tinovella; Azzahra, Vanianissa (Muhammadiyah Medical Journal, 2022)
Background: Corticosteroids are derivatives of steroid hormones that have the effect of inhibiting the inflammatory response. Glucocorticoid is the type of corticosteroid that is easy to obtain and has a high anti-inflammatory effect. Therefore, glucocorticoids are often used in various therapies. However, the use of this drug should be monitored since its side effects can be harmful to the health as paralytic effects or even lethal effects. Purposes: This study aims to determine the behavior of using oral corticosteroids in patients at the Bebita Cicurug Clinic, Sukabumi. Methods: This is a descriptive quantitative research study. Data collection was done from September to December 2019. The respondents of this study were 96 subjects of Bebita Cicurug Clinic with a history of oral glucocorticoid usage. The data was taken using a questionnaire and medical records. Result: The most widely used glucocorticoid type is Methylprednisolone 4 mg and dexamethasone 0,5 mg. Overall, 89.6% of respondents used corticosteroids for a week or less. A total of 21.9% had tried to get corticosteroids without a prescription (self-medication), and all of them didn't get restricted on purchasing corticosteroids. Conclusion: In general, patients in this study had good behavior in using corticosteroids (using steroids according to a doctor's prescription), but 21.9% had tried to get corticosteroids without a prescription, and all of them didn't get restricted on purchasing corticosteroids. Doctors and health workers must clearly explain prescribed drugs' benefits and side effects, especially in patients with chronic diseases. Then ensure that the patient has understood the benefits and side effects of the medications used.